PELATIHAN PEMANFAATAN INTERNET SEBAGAI MEDIA PROMOSI ONLINE DALAM KEGIATAN ONLINE SHOP (OLSHOP) SISWA-SISWI MA SARJI AR-RASYID - Dyan Yuliana; Irma Noervadila; Tri Astindari; Sahwari; Arico Ayani Suparto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
This communityservice activity aims to increase the knowledge and understanding of MA SARJI AR-RASYID students regarding the importance of online promotional media (digital marketing) for their olshop business by utilizing the internet through training activities on the use of the internet as a product promotion media. This training activity was carried out in the XI class of MA SARJI AR-RASYID. This activity is planned to last for 1 day on 15 June 2020 at 09.00 WIB until finished. Resource persons provide material that includes the concept of online promotion, the steps for online promotion, and how to have an effective online product marketing strategy. Furthermore, direct practice of using the internet was carried out to promote the olshop products of class XI MA SARJI AR-RASYID students who were directly guided by 2 sources. The result of this training activity is to increase understanding for XI grade students about the importance of the internet as a product online promotional media and being able to apply it to promote all the olshop products they have, so that it will increase the quantity of sales and increase income to help fulfill their living needs and school fees. as well as in the future development of their products so that they are of higher quality.